Leafhoppers of the genus Batracomorphus (Hemiptera: Cicadellidae: Iassinae) of Kibale National Park, Uganda, with descriptions of seven new species - Helden, Alvin J. (Zootaxa, 2025)
Thirteen leafhoppers of the genus Batracomorphus Lewis, 1834 were identified from Kibale National Park, Uganda. Five previously recognised species were recorded from Uganda for the first time, and the following seven species are described as new: B. ruthae sp. nov.; B. pardos sp. nov.; B. stictopterus sp. nov.; B. chloros sp. nov.; B. eusemos sp. nov.; B. kibalensis sp. nov.; B. ntomino sp. nov.